P0175DETERMINANTS OF RENAL PAPILLARY APPEARANCE IN RENAL STONE FORMERS: AN IN-DEPTH EXAMINATION. (6th June 2020) - Bargagli, Matteo; De Leonardis, Rossella; Ragonese, Mauro; Totaro, Angelo; Pinto, Francesco; Recupero, Salvatore; Bassi, PierFrancesco; Gambaro, Giovanni; Ferraro, Pietro Manuel
Abstract: Background and Aims: Nephrolithiasis is a medical condition characterized by high prevalence among the general population both in Europe and in the U.S. and it is responsible for high costs reaching up to $10 billion per year. It is associated with specific comorbidities such as obesity, arterial hypertension, diabetes mellitus, metabolic syndrome and chronic kidney disease. Kidney stones development is believed to start either from Randall's plaques or from stone plugs. Both these lesions can be seen on renal papillary surfaces, but what promotes the formation of plaques and plugs is not entirely understood. The aim of this study is to investigate the association between the urinary metabolic milieu and a published endoscopic papillary evaluation score (PPLA). We also evaluated the correlation of PPLA score with kidney stone recurrence during follow-up. Method: We prospectively enrolled 31 stone forming patients who undergone retrograde intrarenal surgery procedures. Visual inspection of the accessible renal papillae was performed in order to calculate the PPLA score based on the appearance of ductal plugging, surface pitting, loss of papillary contour and Randall's plaque extension. Demographic information, blood samples, 24h urine collections and kidney stone events during follow-up were collected. Stone composition was analyzed using infrared-spectroscopy. Relative urinary supersaturations (RSS) for calcium oxalate (CaOx), calcium phosphate (CaPi) and uric acid (UA) were calculated using the Equil2 software. PPLA score > 3 was defined as high. Results: Median follow-up period was 11 (min/max 5, 34) months. PPLA score was inversely correlated with BMI (rho = −0.39, p = 0.035) and history of recurrent kidney stones (median PPLA 5.0 vs 2.5, p = 0.029), these results were confirmed when PPLA was considered as a categorical variable (median BMI 27 vs 24, recurrent stone disease 12 vs 62%, p= 0.006). Furthermore, high PPLA score was associated with lower odds of new kidney stone events during follow-up (OR 0.154, 95% confidence interval 0.024, 0.998, p = 0.05). No significant correlations were found between PPLA score, stone composition, blood parameters, 24h urine solute excretions and RSS for CaOx, CaPi and UA. Conclusion: Different papillary abnormalities seem to be linked to specific mechanisms of stone formation. Although data regarding PPLA score are inconsistent, it may be a valid asset for both medical and surgical management of nephrolithiasis. Larger, long-term prospective clinical studies need to be conducted to assess the validity of PPLA score system in evaluating risk of stone recurrence.